Constitutively expressing cell lines that secrete a truncated bovine herpes virus-1 glycoprotein (gpI) stimulate T-lymphocyte responsiveness. - Leary, T P (1992)
The desire to obtain authentically glycosylated viral protein products in sufficient quantity for immunological study has led to the use of eucaryotic expression vectors for protein production. An additional advantage is that these protein products can be studied individually in the absence of their native viral environment. We have cloned a complementary DNA (cDNA) encoding bovine herpes virus-1 (BHV-1) glycoprotein 1 (gpI) into the eucaryotic expression vector, pZipNeo SVX1. Since this protein is normally embedded within the membrane of BHV-1 infected cells, we removed sequences encoding the transmembrane domain of the native protein. After transfection of the plasmid construct into the canine osteosarcoma cell line, D17, or Madin-Darby bovine kidney (MDBK) cells, a truncated BHV-1 (gpI) was secreted into the culture medium as demonstrated by radioimmunoprecipitation and SDS-PAGE. Both a CD4+ T-lymphocyte line specific for BHV-1 and freshly isolated T lymphocytes could recognize and respond to the secreted recombinant gpI. Further, recombinant gpI could elicit both antibody and cellular responses in cattle when used as an immunogen. Having established constitutively glycoprotein producing cell lines, future studies in vaccine evaluation of gpI will be facilitated.